Effect of Strategic Direction on The Performance of Technical Training Institutions in Meru County, Kenya - Muthaa, George M.; Muathe, S.M.A. (Machakos University, 2018)
Organizational performance is important in justifying its existence and resources allocation. To enhance performance, Strategic direction has been identified has useful in promoting organizational performance. For Technical Training Institutions to achieve their core mandate in human resource training, the Government has emphasized on their development and implementation of strategic plans. Technical Training institutions have been operating with strategic plans for at least the last ten years; however no systematic study has been carried out to investigate the influence of these strategic plans on the performance of the institutions. The current study sought to investigate the effects of the strategic direction on performance in respect to enrolment, resources, quality and efficiency. The study used the cross sectional descriptive survey research design. Questionnaires were used for data collection. Instruments were tested for reliability by use of the cronbach’s alpha and a correlation coefficient of 0.75 was obtained. Validity of instruments was ensured by use of peer reviewers and research experts. The researcher personally administered the instruments; this helped in realizing a high return rate. Data was analyzed by use of both descriptive and inferential statistics including frequencies, percentages, means and the regression analyses and presented by use of tables and figures. The study established that the strategic direction had significant influence on the performance of technical training institutions. The introduction of the government policy has a moderating variable improved the model on organizational direction. The researcher recommends the alignment of the institutional philosophy, priorities, innovations and collaborations to the institutional strategic direction which could improve the performance of Technical Training Institutions
Keywords: Strategic Direction